TRACER STUDY PADA PERGURUAN TINGGI ILMU KE-ISLAMAN - REZA FAHMI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The research theme is the concept of business According to Islamic economics. This study aims: (1) Obtaining data about the quality of alumni. (2) Obtaining the absorption data of the world of work. (3) Obtaining data on public confidence in universities. (4) To know the effect of the quality of alumni on the absorption of the world of work and the community's belief in higher education. The sample of research is as many as 201 people. The research results are: (1) There is a relationship between the quality of alumni with public trust. (2) There is an influence of alumni's quality on absorptive capacity of the world of work and public trust.